A REVIEW ON SPECTROPHOTOMETRIC ANALYSIS FOR DRUGS - Bhadoria, Suraj Singh; H Venkatesan; G S Chakraborthy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Through this review article focusing on Application of Spectrophotometric analysis for both Qualitative and Quantitative assay in drug, medicine and remedy standardization. Thereafter it plays a major role in the quality assessment in drug substances.